PENEGAKAN INTEGRITAS DAN ETIKA APARATUR DALAM PELAYANAN KESEHATAN PUBLIK: STUDI KASUS DI RUMAH SAKIT SITI FATIMAH KOTA PALEMBANG - M Dafa Raditya; Muhammad Fitra Alfayed; Sary, Dwy Permata; widya eka stefianesa; Armalisa Nabila Putri S; Arin Juliani; M Fikri Ulumuddin Emp; Riza Adelia Suryani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study aims to analyze the enforcement of integrity and ethics among public healthcare officials at Siti Fatimah Hospital Palembang and examine their influence on service quality and public trust. The research employed a qualitative approach, utilizing in-depth interviews with healthcare workers and patients, as well as observations of ongoing service processes within the hospital environment. Data were analyzed descriptively to gain a comprehensive understanding of how integrity and ethical values are implemented in daily healthcare practices. The findings indicate that healthcare personnel demonstrate professionalism, responsibility, and non-discriminatory treatment toward both BPJS-insured and general patients. The application of integrity and ethics is reflected in courteous behavior, effective communication, empathy toward patients’ conditions, and a service orientation focused on patients’ needs and safety. However, service quality is still affected by limitations in the number of healthcare staff and relatively long waiting times. These challenges are more closely related to systemic and managerial aspects rather than violations of professional integrity. The study concludes that integrity and ethical conduct play a crucial role in enhancing patient satisfaction and strengthening public trust in public healthcare services. Continuous reinforcement of integrity values and improvements in service management are necessary to achieve sustainable and comprehensive service quality enhancement.